2021
DOI: 10.25259/ijdvl_1025_19
|View full text |Cite
|
Sign up to set email alerts
|

Etiological prevalence and antifungal sensitivity patterns of dermatophytosis in India – A multicentric study

Abstract: Background: The prevalence of dermatophytes varies with season, geographical area, socio-economic factors and effective management strategies. Aims: The aim of the study was to assess the prevalence of pathogenic dermatophytes, clinical types of dermatophyte fungal infection, and in vitro antifungal drug susceptibility testing against dermatophytes. Methods: Three hundred and ninety five patients with dermatophytosis were enrolled from five cities (Mumbai, Delhi, Lucknow, Kolkata and Hyderabad) across Indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…This study didn't come across any cases of tinea capitis which involves the scalp region which is more commonly seen in children and also tinea manuum which involves one or both hands. The previous studies have also concluded that other than tinea incognita, tinea corporis is the most prevalent type compared to the other clinical types of dermatophytoses 5,32–34 …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This study didn't come across any cases of tinea capitis which involves the scalp region which is more commonly seen in children and also tinea manuum which involves one or both hands. The previous studies have also concluded that other than tinea incognita, tinea corporis is the most prevalent type compared to the other clinical types of dermatophytoses 5,32–34 …”
Section: Discussionmentioning
confidence: 98%
“…The previous studies have also concluded that other than tinea incognita, tinea corporis is the most prevalent type compared to the other clinical types of dermatophytoses. 5,[32][33][34] In the analysis of KOH mount and culture findings, out of all the sample specimens, there were 89% KOH mount, and 81% were culture isolates positive for dermatophytosis. In this present study, T. rubrum (61%) was the most predominant dermatophyte isolated also described by this studies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, one of these studies shows no effect on relapse rate between 100 mg, 200 mg or 400 mg per day regime of ITZ. The majority of recent studies suggest MIC for ITZ against the trichophyton group of fungi remains low well within the upper normal limit of wild‐type strains 19,20 . Study by Khurana et al 21 .…”
Section: Discussionmentioning
confidence: 99%
“…The majority of recent studies suggest MIC for ITZ against the trichophyton group of fungi remains low well within the upper normal limit of wild-type strains. 19,20 Study by Khurana et al 21 demonstrated that plasma levels of ITZ above 0.2 μg/mL are consistently associated with therapeutic success which can be easily achieved with 100 mg/day doses of the drug. Dose of ITZ (200 mg/ day), recommended by various guidelines and routinely prescribed by dermatologist in India is well above this threshold.…”
Section: Ta B L Ementioning
confidence: 99%
“…Available studies from India and abroad suggest that the prevalent species of the present epidemic of dermatophytosis in India exhibits low MIC for ITZ as yet. [ 15 16 ] There are no widespread reports of increase in MIC or any genetic mutation linked to reduce the susceptibility of Trichophyton genera of dermatophytes to ITZ.…”
Section: Methodsmentioning
confidence: 99%